Bibliometric Analysis of Forensic Accounting Research Trends in Countering Fraud in the Public Sector - Loso Judijanto; Siska Yulia Defitri (West Science Accounting and Finance, 2024)
This bibliometric study investigates the evolving landscape of forensic accounting, with a focus on fraud detection and prevention in the public sector. Utilizing data from prominent academic databases, the research highlights the integration of advanced technological tools and data analytics into traditional forensic accounting practices. The analysis identifies key themes and emerging trends within the field, such as the increasing importance of technology, the need for regulatory adaptation, and the expansion of forensic accounting into new areas like social network analysis and economic crime. The findings emphasize the shift towards a more sophisticated, interdisciplinary approach necessary for tackling complex financial crimes in a globalized economy. The study not only provides a comprehensive overview of the current state of forensic accounting research but also suggests directions for future academic and practical applications, underlining the critical role of continuous education and international cooperation in enhancing the effectiveness of fraud prevention strategies.